Situation Report: Poland, 29 August 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reshuffles in the Party and in the Media / by Anna Swidlicka The First Political Prisoners Released / by Anna Pomian Will Wladyslaw Frasyniuk Regain His Freedom? / by Michal Kolodziej Political Aspects of the Clemency Law / by Anna Swidlicka The Labor Situation / by Anna Swidlicka "Sanitary Terror" Declared to Fight Filth Independent Groups Warn of Potential Ecological Catastrophe August: A Month of Sobriety? / by Anna Pomian